Pengaruh Kesadaran Merek, Asosiasi Merek, Kualitas Produk Dan Harga Terhadap Loyalitas Pelanggan Pada Produk Jamu Tolak Angin Cair Di Toko Nirmala Brebes - Azzah Hanifah; Tri Octaviani; Slamet Bambang Riono; Muhammad Syaifulloh; Syariefful Ikhwan (CV. Aksara Global Akademia, 2023)
Effective marketing programs and efforts to educate consumers about the efficacy and use of products can help create greater awareness and build loyalty. This study investigated the influence between brand awareness, brand association, product quality, product price, and customer loyalty on Tolak Angin products at Nirmala Brebes Store. The population of this study was Tolak Angin customers at the Nirmala Brebes Store. The sample was taken 25% of the population of 412 people, so 103 respondents were obtained. The results showed that brand awareness has a positive and significant effect on customer loyalty, brand associations have a positive and significant effect on customers, product quality has a positive and significant effect on customers, price has a positive and significant effect on customers. Simultaneously, brand awareness, brand association, product quality, and product price have an influence on customer loyalty of Tolak Angin products at Nirmala Brebes Store by 84.4%.